Islamic Boarding School Education Cultivates Moderate Character in Poso Central Sulawesi - Sah, Moh. Arief; Fuad, A. Jauhar (Al-Hayat: Journal of Islamic Education, 2024)
This study is oriented to describe and interpret the phenomenon of plural life in Islamic boarding schools and their environments. This study is based on empirical data obtained through the concept and internalization of religious moderation values ​​in three locations directly related to the Poso conflict, namely Walisongo 1 Poso Islamic Boarding School, Amanah Putera Islamic Boarding School, and Gontor Poso Islamic Boarding School. This study uses a qualitative approach and phenomenological types and case studies. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques are interpretative phenomenological analysis and multisite analysis because there is more than one locus. The validity of the data uses triangulation techniques of source data, theory, and methods. The study results indicate that the values ​​of religious moderation applied are conceptualized through the curriculum's vision, mission, and role in Islamic boarding schools. Moderate character education of students through internalization techniques can be reviewed in three dimensions; a) the process of developing, renewing and adjusting paradigms by the times, implementing moderate curriculum and learning; b) the process of integrating the values ​​of moderation with a set of subjects in Islamic boarding schools; c) a more profound process using verbal communication in embodying the values ​​of moderation in daily behavior in Islamic boarding schools and social environments. This research is only in the corridor of the Islamic boarding school environment, where all educational processes are coordinated directly by the head of the boarding school, so further study is needed in different models and environments. The results of this study emphasize the importance of education in instilling and helping to foster moderate character in students.